2021
DOI: 10.1002/adma.202103593
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination Flow Repressors: Enhancing Wound Healing of Infectious Diabetic Ulcers through Stabilization of Polyubiquitinated Hypoxia‐Inducible Factor‐1α by Theranostic Nitric Oxide Nanogenerators

Abstract: Current treatments for diabetic ulcers (DUs) remain unsatisfactory due to the risk of bacterial infection and impaired angiogenesis during the healing process. The increased degradation of polyubiquitinated hypoxia‐inducible factor‐1α (HIF‐1α) compromises wound healing efficacy. Therefore, the maintenance of HIF‐1α protein stability might help treat DU. Nitric oxide (NO) is an intrinsic biological messenger that functions as a ubiquitination flow repressor and antibacterial agent; however, its clinical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 44 publications
3
75
0
Order By: Relevance
“…VEGF secreted by vascular endothelial cells is a crucial factor that facilitates neovascularization following endothelial recruitment and regeneration. [ 55 ] It is generally recognized that HIF and VEGF expression are positively associated with each other. [ 56 ] Thus, we next sought to study the effects of hypoxia‐preconditioned exosomes treatments on the expression of HIF‐1α.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF secreted by vascular endothelial cells is a crucial factor that facilitates neovascularization following endothelial recruitment and regeneration. [ 55 ] It is generally recognized that HIF and VEGF expression are positively associated with each other. [ 56 ] Thus, we next sought to study the effects of hypoxia‐preconditioned exosomes treatments on the expression of HIF‐1α.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, angiogenesis is crucial in the wound healing process, and previous investigations showed that poor vascularization contributed to diabetic wound healing delay. The proliferation, migration, and tube formation of endothelial cells are the main parts of the angiogenesis process [ 54 ]. In this study, the PCL/VMT composite scaffolds promoted L929 and MAEC cell adhesion and proliferation and promoted cell migration and tube formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, NO is used as a gas drug for the treatment of diabetic wounds [ 213 , 215 , 216 ], but its clinical application in the treatment of diabetic ulcers (DU) has been hindered by the difficulty in controlling the release of NO. To solve this problem, Yiqi Yang et al proposed a smart near-infrared (NIR)-triggered NO nanogenerator (SNP@UCM) to precisely regulate the release of NO [ 153 ]. In this study, sodium nitroprusside (SNP) was used as the NO donor, and upconversion nanoparticles (UCNPs) were used as the core of the nanogenerator to convert the deep-tissue-penetrating near-infrared signal into visible light in situ ( Figure 9 ).…”
Section: Application Of Mofs In Wound Healingmentioning
confidence: 99%
“…sO2: oxygen saturation. * p < 0.05, ** p < 0.01.Reproduced with permission [ 153 ]. Copyright 2021, Advanced materials .…”
Section: Figurementioning
confidence: 99%